Near-Infrared Data Acquisition for the VERITAS 2023 Iceland Field Campaign - Adeli, S.; Garland, Stephen Patrick; Nunes, Daniel C.; Smrekar, Suzanne E.; Mueller, Nils; Domac, Akin; Alemanno, Giulia; Hamilton, Christopher W.; Pedersen, Gro; Cascioli, G.; Mazarico, E.; Jozwiak, Lauren M.; et al. (2024)
The composition of lava fields on Venus and their alteration state are poorly constrained. The Venus Emissivity Mapper (VEM) [1, 2] on board NASAs Venus Emissivity, Radio Science, InSAR, Topography and Spectroscopy (VERITAS) mission [3] and its twin VenSpec-M on ESA’s EnVision mission will observe the surface of Venus in the NIR range through five atmospheric windows covered by six spectral bands. These will enable studying the spectral characteristics of the Venusian surface, as well as lava types and possible alteration processes. To prepare for these missions and deepen our understanding of the emissivity spectral characterization of various volcanic rocks, we developed a field camera system analogous to VEM, named VEMulator, and have undertaken in-situ measurements in the spectral range of the VEM instrument during field work at Venus analogue sites. We will relate these data to emissivity spectra of field samples collected in the Venus chamber at the Planetary Spectroscopy Laboratory (PSL) of DLR-Berlin [1]. The VERITAS expedition in Iceland, in early August 2023 [4, 5] addressed these objectives. This expedition included DLR airborne synthetic aperture radar (SAR) data, collected in X-band, similar to VERITAS, and S-band, similar to Magellan and EnVision. The ground team collected surface topography and roughness using LiDAR scanners [6, 7] and permittivity [8] as ground truthing for the airborne SAR data. We acquired NIR data using the VEMulator 2.0 (Fig. 1), which uses similar NIR spectral range to VEM surface channels (0.86-1.2 um).